Non-covalent interactions in biomacromolecules - Cerný, Jirí; Hobza, Pavel (Physical chemistry chemical physics, 2007)
Non-covalent interactions play an important role in chemistry, physics and especially in biodisciplines. They determine the structure of biomacromolecules such as DNA and proteins and are responsible for the molecular recognition process. Theoretical evaluation of interaction energies is difficult; however, perturbation as well as variation (supermolecular) methods are briefly described. Accurate interaction energies can be obtained by complete basis set limit calculations providing a large portion of correlation energy is covered (e.g. by performing CCSD(T) calculations). The role of H-bonding and stacking interactions in the stabilisation of DNA, oligopeptides and proteins is described, and the importance of London dispersion energy is shown.
Keywords: konformace nukleové kyseliny; Hydrogen Bonding; vodíková vazba; molekulární modely; termodynamika; Nucleic Acid Conformation; Base Pairing; Proteins; Thermodynamics; Hydrophobic and Hydrophilic Interactions; DNA; hydrofobní a hydrofilní interakce; Models, Molecular; proteiny; párování bází